Modulation of Calcium Transients in Cardiomyocytes by Transient Receptor Potential Canonical 6 Channels - Ahmad, Azmi A.; Streiff, Molly E.; Hunter, Chris; Sachse, Frank B. (Frontiers in Physiology, 2020)
Transient receptor potential canonical 6 (TRPC6) channels are non-selective cation channels that are thought to underlie mechano-modulation of calcium signaling in cardiomyocytes. TRPC6 channels are involved in development of cardiac hypertrophy and related calcineurin-nuclear factor of activated T cells (NFAT) signaling. However, the exact location and roles of TRPC6 channels remain ill-defined in cardiomyocytes. We used an expression system based on neonatal rat ventricular myocytes (NRVMs) to investigate the location of TRPC6 channels and their role in calcium signaling. NRVMs isolated from 1-2 day old animals were cultured and infected with an adenoviral vector to express enhanced-green fluorescent protein (eGFP) or TRPC6-eGFP. After 3 days, NRVMs were fixed, immunolabeled and imaged with confocal and super-resolution microscopy to determine TRPC6 localization. Cytosolic calcium transients at 0.5 and 1 Hz pacing rates were recorded in NRVMs using indo-1, a ratio-metric calcium dye. Confocal and super-resolution microscopy suggested that TRPC6-eGFP localized to the sarcolemma. NRVMs infected with TRPC6-eGFP exhibited higher diastolic and systolic cytosolic calcium concentration as well as increased sarcoplasmic reticulum (SR) calcium load compared to eGFP infected cells. We applied a computer model comprising sarcolemmal TRPC6 current to explain our experimental findings. Altogether, our studies indicate that TRPC6 channels play a role in sarcolemmal and intracellular calcium signaling in cardiomyocytes. Our findings support the hypothesis that upregulation or activation of TRPC6 channels, e.g. in disease, leads to sustained elevation of the cytosolic calcium concentration, which is thought to activate calcineurin-NFAT signaling and cardiac hypertrophic remodeling. Also, our findings support the hypothesis that mechanosensitivity of TRPC6 channels modulates cytosolic calcium transients and SR calcium load.